Levator Function in Blepharoptosis Surgery - NUHOĞLU, FADİME; Nuhoglu, FADİME; OZDEMIR, Fatma Esin; KARADEMIR, Zeliha; ELTUTAR, Kadir (My University, 2013)
Aim To investigate the predictive value of levator function in the outcomes of surgeries using the anterior levator resection technique in patients with aponeurotic blepharoptosis.